A Graphene Oxide Nano-Sheets: A Novel Eco-Friendly Approach for Tissue Engineering and Antibacterial Applications in Bone Disease - Abdullah, Hind W.; Mubarak, Tahseen H; Resan, Kadhim K. (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Obtaining novel scaffolds on bone disease-affected cells with osteoconductivity has recently been the focus of tissue engineering methodologies. Chemical treatment and microwave radiation form a novel strategy to create graphene oxide nanosheets (Gns) that decorate carbon crystal structures. This approach is proven to be eco-friendly. Gns was characterized using